ANTIDIABETIC POTENTIAL OF SOURSOP LEAF EXTRACT (Annona muricata L.) AS A TREATMENT FOR TYPE 2 DIABETES MELLITUS - Annisa Ratya (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Type 2 Diabetes Mellitus (DM) is a disease or chronic metabolic syndrome that marked by high level blood glucose with insulin insuficience. Indonesia has been the 4th largest diabetics in the world. The therapy of DM is oral antidiabetic, including expensive drugs with some side effects, so that herbal medicine begins to attract the attention. One of the herbal medicine that has been used as antidiabetic is soursop (Annona muricata L.), especially the leaf, because it become the most widely used plants as antidiabetic herbal. One of active compounds in soursop leaf that used as antidiabetic is tannin that can be hydrolyzed to gallotanin and ellagitanin which has insulin-like compound, and flavonoids, especially quercenin, to stimulate pancreatic insulin secretion and repair the damage of  β cells pancreas. Besides that both tannins and flavonoids are inhibitors of the α-glucosidase enzyme. The soursop leaf extract can be used as an alternative traeatment for type 2 DM.[J Agromed Unila 2014; 1(1):61-6] Keywords: quercenin, soursop leaf, tannin, type 2 diabetes mellitus